PENGARUH GAYA KEPEMIMPINAN, MOTIVASI DAN INSENTIF TERHADAP KINERJA PEGAWAI DINAS PERHUBUNGAN KABUPATEN PENAJAM PASER UTARA - Ponamon , Triana; Hadiyatno, Didik; Yuliani, Tutik (MEDIA RISET EKONOMI [MR.EKO], 2025)
The purpose of this study was to determine the effect of leadership style, motivation and incentives on the performance of Employees of the North Penajam Paser District Transportation Office. This research was conducted at the North Penajam Paser Regency Transportation Service, with 35 respondents, this research method used quantitative methods. Data collection by observation and distributing questionnaires using Google From. The data analysis technique used is multiple linear analysis by conducting instrument tests, classical assumption tests, and partial hypothesis testing (t-test). The results showed that the variables of leadership style, motivation and incentives had a positive and significant effect on the job satisfaction performance of Employees of the Department of Transportation, North Penajam Paser Regency